2017
DOI: 10.1111/are.13406
|View full text |Cite
|
Sign up to set email alerts
|

Single nucleotide polymorphisms in the growth hormone gene ofOreochromis niloticusand their association with growth performance

Abstract: Polymorphisms in the growth hormone (GH) gene that is associated with the growth rate of farmed fish have been the target of many breeding programmes. The present study aimed to identify single nucleotide polymorphisms (SNPs) in GH gene regions to evaluate the association of SNP variations with the growth rate of two Nile tilapia: Oreochromis niloticus (Linnaeus, 1758) strains. The targeted regions were amplified, sequenced, aligned and screened for the presence of SNPs; thereafter, performance tests were used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 47 publications
1
12
0
Order By: Relevance
“…Jaser et al. (2017) identified SNPs in the promoter region of the GH gene of a hatchery population of Nile tilapia and associated the markers with individual growth rate. Li et al.…”
Section: Discussionmentioning
confidence: 99%
“…Jaser et al. (2017) identified SNPs in the promoter region of the GH gene of a hatchery population of Nile tilapia and associated the markers with individual growth rate. Li et al.…”
Section: Discussionmentioning
confidence: 99%
“…The second study carried out a more extensive search for SNPs in the promoter and intron-I of two strains of Nile tilapia. As a result, a significant association was found between the promoter's SNPs and growth rate using a univariate linear mixed model (Jaser et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Data were obtained from two genetically distinct strains of Oreochromis niloticus, Red-Stirling and Chitralada, and their crossbreeds. Seven genetic groups were obtained by backcross breeding (Lago et al, 2017), as shown in Table 1. The progenies from the seven genetic groups were obtained in mating hapas (8 × 6 × 2 m 3 ) using one dam with two sires after two-week intervals to synchronize spawning (Tsadik, 2014).…”
Section: Origin Of Genetic Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Enhanced growth is a known attribute of the O. niloticus species and the main selection drive within the GIFT selection programme (Ponzoni et al, 2011), so perhaps a proportion of the O. niloticus SNP panel could reflect a growth advantage. Efforts on ongoing to unravel the genetic basis for growth selection with polymorphisms in the growth hormone gene implicated in O. niloticus (Jaser et al, 2017) and multiple linkage groups (LGs) associated with growth in saline tolerant hybrid tilapia derived from O. mossambicus and Asian red tilapia (Lin et al, 2016).…”
Section: Diagnostic Snp Markers and Trait Associationmentioning
confidence: 99%